2023
DOI: 10.1021/acs.jafc.3c04247
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Binding Capabilities in an Ecologically Important Odorant Receptor of the Fall Armyworm, Spodoptera frugiperda, by a Single Point Mutation

Xiaohe Liu,
Longfei Shi,
Adel Khashaveh
et al.

Abstract: Olfaction plays a crucial role in locating food sources, mates, and spawning sites in the fall armyworm (FAW), Spodoptera f rugiperda (Lepidoptera: Noctuidae). In the current study, SfruOR14, a highly conserved odorant receptor (OR) in lepidopteran species, was newly uncovered in S. f rugiperda. In two-electrode voltage clamp recordings, the SfruOR14/Orco complex was narrowly tuned to six volatile compounds including phenylacetaldehyde (PAA), benzaldehyde, heptaldehyde, (E)-2-hexen-1-al, cinnamaldehyde, and 2-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 49 publications
0
0
0
Order By: Relevance
“…These findings indicate that residues Thr142, Gln80, Gln282, and Thr312 together formed the key binding site in the active pocket for the aldehyde ligands. Previous studies have demonstrated the importance of a single key residue, such as His83 of the SfruOR14 in the fall armyworm Spodoptera frugiperda, in biasing the receptor against certain ligands . Similarly, the Ser209 residue was found to be essential for the OachOR16 binding with camphor in Orthaga achatina .…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…These findings indicate that residues Thr142, Gln80, Gln282, and Thr312 together formed the key binding site in the active pocket for the aldehyde ligands. Previous studies have demonstrated the importance of a single key residue, such as His83 of the SfruOR14 in the fall armyworm Spodoptera frugiperda, in biasing the receptor against certain ligands . Similarly, the Ser209 residue was found to be essential for the OachOR16 binding with camphor in Orthaga achatina .…”
Section: Resultsmentioning
confidence: 94%
“…Site-directed mutagenesis was performed based on docking analysis. Three mutant variants were designed . Type I: Thr142 replaced with Ala; Type II: Gln80, Gln282, and Thr312 replaced with Ala; Type III: All four residues (Thr142, Gln80, Gln282, and Thr312) were replaced with Ala. Wild-type and mutant MmedOR48 constructs in pT7TS were synthesized by Sangon Biotech (Shanghai, China).…”
Section: Methodsmentioning
confidence: 99%